2015
DOI: 10.1128/jvi.00842-15
|View full text |Cite
|
Sign up to set email alerts
|

Naturally Occurring Capsid Protein Variants of Human Papillomavirus Genotype 31 Represent a Single L1 Serotype

Abstract: We investigated naturally occurring variation within the major (L1) and minor (L2) capsid proteins of oncogenic human papillomavirus (HPV) genotype 31 (HPV31) to determine the impact on capsid antigenicity. L1L2 pseudoviruses (PsVs) representing the three HPV31 variant lineages, variant lineages A, B, and C, exhibited comparable particle-to-infectivity ratios and morphologies. Lineage-specific L1L2 PsVs demonstrated subtle differences in susceptibility to neutralization by antibodies elicited following vaccina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 65 publications
(84 reference statements)
0
15
0
Order By: Relevance
“…Codon-optimized L1 and L2 genes representing consensus lineage and sublineage variant sequences (Supplementary Figure 1) were synthesized (GeneArt; Thermo Fisher Scientific) with additional site-directed mutagenesis (QuikChange Site-Directed Mutagenesis Kit, Agilent Technologies) as required [8–12]. Inserts were confirmed by Sanger sequencing.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Codon-optimized L1 and L2 genes representing consensus lineage and sublineage variant sequences (Supplementary Figure 1) were synthesized (GeneArt; Thermo Fisher Scientific) with additional site-directed mutagenesis (QuikChange Site-Directed Mutagenesis Kit, Agilent Technologies) as required [8–12]. Inserts were confirmed by Sanger sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…For each genotype, a single serial dilution series of each serum was tested against all relevant variant PsVs in parallel. The titer of each serum against each variant PsV was compared to that generated against the consensus A/A1 variant PsV and a fold difference metric was generated to allow normalization and intra-/intergenotype comparisons [8–12].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1D). All HPV45 variant PsVs displayed similar particle sizes (median, 55 nm; interquartile range [ IQR], 53 to 57 nm) and particle-to-infectivity ratios (27) (median, 2.9 ϫ 10 2 ; IQR, 2.0 ϫ 10 2 to 4.7 ϫ 10 2 ). Sera from 12-to 15-year-old girls, collected following three doses of Cervarix or Gardasil HPV vaccine (22), were used to assess HPV45 sublineage variant sensitivity to cross-neutralizing antibodies ( Fig.…”
Section: ϫ8mentioning
confidence: 99%
“…Single-cycle replication-incompetent pseudoviruses (PsVs) representing HPV16 L1, but not L2, variants (26) appear to exhibit little difference in their susceptibilities to type-specific antibodies elicited by HPV16 virus-like particles (VLP). We recently demonstrated that although PsVs incorporating HPV31 L1 and L2 lineage variants (A, B, and C) were susceptible to cross-neutralizing antibodies elicited by the Cervarix and Gardasil HPV vaccines, there were lineage-specific differences in sensitivity (27). Here we examine the potential impact of lineage-specific L1 and L2 HPV45 variation on sensitivity to cross-neutralizing antibodies elicited by the Cervarix and Gardasil HPV vaccines.…”
Section: ϫ8mentioning
confidence: 99%